Swelling pressure of phyllite residual soil during saturation - Zhang, Qin; Qin, Liuyang; Tang, Hao; Yan, Mengqiu; Ji, Jingru; Yang, Wenzhou; Yan, Rongtao (Frontiers in Materials, 2024)
Phyllite residual soil is a typical regional soil formed from the weathering of phyllite rock formations, characterized by poor engineering properties. The swelling pressure could pose a threat to roadbed stability and other geological engineering disasters during the rainy season. Therefore, studying the swelling pressure of phyllite residual soil is critical for ensuring the sustainable development of both human society and the natural environment. In this study, a series of swelling pressure tests were conducted on the phyllite residual soil to determine its swelling pressure, and nuclear magnetic resonance (NMR) test was applied to assess the evolution of soil fabric in both the initial unsaturated state and saturated state. The results indicate that the swelling rate of phyllite residual soil is negatively correlated with the initial water content and positively correlates with the dry density. The denser or drier the phyllite residual soil is in its initial state, the higher the equilibrium swelling pressure will be.The analysis of T2 distribution curves reveals that during the wetting process in phyllite residual soil, water fills micropores prior to macropores until water fills up all pores.